Bioelectrical Impedance Analysis of Water Reduction in Lower-Limb Lymphedema by Lymphaticovenular Anastomosis - Yasunaga, Yoshichika; Yanagisawa, Daisuke; Ohata, Erika; Matsuo, Kiyoshi; Yuzuriha, Shunsuke (Journal of Reconstructive Microsurgery, 2019)
Background Although lymphedema is fundamentally abnormal accumulation of excess water in the extracellular space, previous studies have evaluated the efficacy of physiological bypass surgery (lymphaticovenular anastomosis [LVA]) for lymphedema without measuring water volume. This study clarified the water reductive effect of LVA using bioelectrical impedance analysis (BIA).Methods The efficacy of LVA for unilateral lower-limb lymphedema was evaluated using BIA in a retrospective cohort. The water volume of affected and unaffected legs was measured using multifrequency BIA before and after LVA. Preoperative measurements were undertaken after compression therapy for at least 3 months. The follow-up period after LVA was a minimum of 6 months.Results Thirty consecutive patients with unilateral lower-limb lymphedema were enrolled. The mean water volume reduction of the affected leg by LVA (ΔLBW) was 0.86 L (standard deviation [SD]: 0.86, median: 0.65) with a mean number of 3.3 anastomoses (SD: 1.7). The mean reduction rate of edema was 45.1% (SD: 36.3). Multiple linear regression analysis revealed water volume difference between the affected and unaffected legs before LVA (excess LBW) as the strongest predictor of ΔLBW (R2 = 0.759, p < 0.01; β = 0.500, p < 0.01).Conclusion The LVA reduces the volume of accumulated body water in lower-limb lymphedema. As excess LBW most strongly predicted the amount of water volume reduction by LVA, body water volume measurement by BIA before LVA might identify patients with low excess LBW not expected to benefit from LVA, regardless of apparent differences in limb circumference.
Keywords: lymphedema; lymphaticovenular anastomosis; bioelectrical impedance analysis